2009
DOI: 10.1093/icesjms/fsp218
|View full text |Cite
|
Sign up to set email alerts
|

Swimbladder condition and target strength of myctophid fish in the temperate zone of the Northwest Pacific

Abstract: Yasuma, H., Sawada, K., Takao, Y., Miyashita, K., and Aoki, I. 2010. Swimbladder condition and target strength of myctophid fish in the temperate zone of the Northwest Pacific. – ICES Journal of Marine Science, 67: 135–144. We report theoretical values of the target strength (TS) of four myctophid fish (Ceratoscopelus warmingii, Myctophum asperum, Diaphus garmani, and Diaphus chrysorhynchus) based on morphometry of the swimbladder. None of the D. chrysorhynchus had an inflated swimbladder, but the other specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 27 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…Catches were dominated by species with functional swimbladders as adults (Davison, 2011) which are strong scatterers. However, swimbladder resonance of myctophids and other mesopelagic fishes seems to increase with depth depending on swimbladder size, potentially biasing estimates of backscatter in deeper waters (Kloser et al, 2002;Godø et al, 2009;Yasuma et al, 2010). The effects of this bias in our estimates will be discussed below.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Catches were dominated by species with functional swimbladders as adults (Davison, 2011) which are strong scatterers. However, swimbladder resonance of myctophids and other mesopelagic fishes seems to increase with depth depending on swimbladder size, potentially biasing estimates of backscatter in deeper waters (Kloser et al, 2002;Godø et al, 2009;Yasuma et al, 2010). The effects of this bias in our estimates will be discussed below.…”
Section: Discussionmentioning
confidence: 90%
“…As the horizontal range of myctophids increases, estimates of volume backscattering strength decrease. Swimbladder resonance increases acoustic backscatter from fishes and such effect is more pronounced at greater depths (>300 m) (Godø et al, 2009;Yasuma et al, 2010). Consequently, bias from swimbladder resonance mainly affects daytime acoustic observations, when mesopelagic fish occur deeper in the water column.…”
Section: Discussionmentioning
confidence: 99%
“…and pearlside in the ECS were estimated based on acoustic survey [6], biomass of micronekton in the ECS was not estimated because the target strength of the species was not reported. Subsequently, Yasuma et al [7] reported the target strength of Diaphus garmani and D. chrysorhynchus, and therefore the biomass of the micronekton in the ECS could be estimated in the present study. The first purpose of this study was to determine whether the biomass of mesopelagic fish in the ECS is substantial or not based on the acoustic method.…”
Section: Introductionmentioning
confidence: 64%
“…In particular, myctophids are difficult to identify to species level using underwater acoustics and further studies are required to gain new insight into the TS relationships and acoustic backscattering properties of myctophid species. New approaches, such as acoustic morphometric descriptors/classification (Charef et al, 2010;Korneliussen and Ona, 2003), in situ TS probes and theoretical TS modelling (Yasuma et al, 2003;Yasuma et al, 2010), together with continued acoustic surveys and scientific netting, are likely to develop the field of myctophid acoustics. However, there is clearly a pressing need to acquire basic data on these fish and their schooling behaviour in these high latitude regions that are experiencing rapid environmental change.…”
Section: Discussionmentioning
confidence: 99%